Southwest Research-Extension Center, Field Day 2012 (Kansas Agricultural Experiment Station Research Reports, 2012)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: crops; tillage; soil fertility; weed science; SRP1070; 2012